JavaServer faces : - Schalk, Chris (Mcgraw-Hill, 2007)
Ideal for the 3+ million Java developers, this fast-paced tutorial offers in-depth coverage of JavaServer Faces (JSF) -- Sun Microsystem's Web application architecture for the future. Co-written by the #1 JSF expert in the Java community, this book offers the most complete resource on JSF available. . * Extensive coverage on JSF custom component development. * Serves as a thorough introduction to AJAX technology and techniques. * Numerous custom JSF component examples including AJAX enabled components provided.